Calculus: Early Transcendentals (2nd Edition)

Published by Pearson
ISBN 10: 0321947347
ISBN 13: 978-0-32194-734-5

Chapter 3 - Derivatives - 3.4 The Product and Quotient Rules - 3.4 Exercises: 39

Answer

$g'(t) = 6t - \frac{42}{t^8}$

Work Step by Step

$g(t) = 3t^2+\frac{6}{t^7} = 3t^2 + 6t^{-7}$ Power rule: $g'(t) = 3(2)t^{(2-1)} + 6(-7)t^{(-7-1)} = 6t - \frac{42}{t^8}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.